Method for Valorization of Coffee Cherry Waste via Hydrothermal Valorization Using Organic and Inorganic Acids as Catalysts - Alejandra Sophia Lozano Pérez; Valentina Romero Mahecha; Carlos Alberto Guerrero Fajardo (Methods and Protocols)
The valorization of coffee cherry waste through hydrothermal carbonization (HTC) was investigated using various organic and inorganic acid catalysts to produce platform chemicals. This study aimed to evaluate the effectiveness of these catalysts for enhancing reaction rates, improving yields, and promoting selectivity. The results showed that sulfuric acid and adipic acid were the most effective, each resulting in a 20% increase in the total yield, demonstrating the potential of organic acids as efficient catalysts in HTC. Other catalysts, such as benzoic acid and phenylacetic acid, also showed promising results, while butyric acid significantly decreased the total yield. The most abundantly produced platform chemicals were sugars, followed by formic acid, levulinic acid, HMF, and furfural. These findings highlight the potential of coffee cherry waste as a valuable resource for producing key chemicals, and the feasibility of hydrothermal carbonization as a sustainable approach for biomass valorization. This study emphasizes the importance of selecting the appropriate catalysts to optimize the conversion process and maximize the extraction of valuable chemicals. The environmental and economic implications of these findings are significant, as they can contribute to the development of sustainable and efficient biomass utilization technologies that could transform agricultural waste into high-value products while reducing waste and promoting a circular economy.